Fiber Reinforced Composite a forgotten sword in prosthodontics - Lanzara, Rajat (International Journal of Scientific Research and Management (IJSRM), 2022)
Prosthodontics is a constantly evolving branch of dentistry as a result of innovative treatment options based on new materials, treatment techniques, and technologies, with composite material revolutionised everything. With the advent of fiber reinforcement, it has further increased the potential uses of composites within dentistry. Fiber reinforced materials have highly favourable mechanical properties and their strength to weight ratios are superior to those of most alloys. When compared to metals they offer many other advantages as well, including non-corrosiveness, translucency, good bonding properties and ease of repair. They also offer the potential for chairside and laboratory fabrication. This article describes the use of fiber reinforced composites in Prosthodontics and also in other disciplines in dentistry.